Enhancing Ressourcement: Johann Adam Möhler's Retrieval of Anselm. (June 2023) - Kaplan, Grant
This article begins by suggesting a wider or more formal understanding of the movement known as ressourcement . After engaging a recent volume of essays on retrieval, the article takes up the work of one contemporary and one bygone theologian in order to highlight how their work embodies the call for a broader understanding of returning to the sources. It then uses Johann Adam Möhler's reading of Anselm and later medieval theology as exemplary of this call.